Penerapan Pola Habituasi Dalam Membentuk Altruisme Siswa di MAN Sampang dan MAN 1 Pamekasan - Zulaicha; Hasan, Nor; Zainab, Nurul (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to examine habituation patterns in shaping students' tolerance attitudes in the school environment as part of character education efforts. Habituation or habituation is an effective method in instilling the values of tolerance through activities that are carried out regularly, consistently, and in a directed manner. To answer this problem, research is carried out with a qualitative approach, a type of case study research with a multi-site design. The research location was chosen by MAN Samapang and MAN 1 Pamekasan. Data collection was carried out by semi-structured interviews: school principals, curriculum leaders, teachers of religious beliefs and students. non-participant observations, and documentation. Data analysis is carried out in two stages: data condensation, data presentation and conclusion drawn. Checking the validity of data through credibility, transferability, dependability and objectivity tests. The results of his research are that the application of habituation patterns in MAN Sampang and MAN 1 Pamekasan is effective in forming students' altruistic character through routine activities such as welcoming students, ubudiyah activities, shadaqah, and Clean Friday. This activity instills the values of empathy, responsibility, discipline, and social concern, and is an important part of the character education strategy that is integrated into students' daily lives